Dwaya Rupa Penggambaran Dua Karakter Dalam Satu Tokoh - Wiwin Sari Putri, Ni Komang; kustiyanti, dyah; Ayu Desiari, Made (Jurnal IGEL : Journal Of Dance, 2024)
This article discusses the creation of a new creative dance work that originates from the Panji Semirang story, the search for Galuh Candra Kirana when she disguised herself as Panji Semirang to look for her lost lover. The idea for this dance work is motivated by the phenomenon that exists around that when someone wants to be what other people want in order to be liked or respected by other people, they often forget their own identity. The purpose of creating a dance work. These are: (1) Inviting people to develop their creativity and improve their abilities in the art of dance, to create an original creative work through the processing and development of movement; (2) Become a source of reference for new works that will be created in the future; (3) To contribute to the progress and brilliance of dance creation in collaboration with the Wayan Geria Foundation. The process or stages of creation that are followed include: (1) Ngarencana, (2) Nuasen, (3) Makalin, (4) Nelesin, and (5) Ngebah. This work is realized in the form of a new dance creation consisting of seven female dancers depicting the characters Galuh Candra Kirana and Panji Semirang. The structure of this work is divided into three parts, namely beginning, content, and ending. The dance accompaniment used in this work is Gamelan Selonding with the addition of several instruments such as drums, flute, gentorag, cengceng ricik, and gong. This dance uses modified Balinese dance make-up and a semi-contemporary style fashion concept. The results of the dance creation process were performed at the Natya Mandala Building, Indonesian Institute of the Arts, Denpasar.